PENYEBAB MENINGKATNYA PERKAWINAN DI BAWAH UMUR DI KANTOR URUSAN AGAMA KECAMATAN KEBAKKRAMAT TAHUN 2019-2021 - Widiyati, Wahyu; Syamsuddin, S; Baehaqi, B (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
Underage marriage is a marriage or contract that can guarantee that a man and a woman have each other and can have husband-wife relations and that marriage is carried out by a person (potential husband, prospective wife) who has not reached the age specified by law. The current law in Indonesia that has been determined by the government. Namely under the age of 19 for men and women in accordance with Law Number 16 of 2019. This study uses a qualitative descriptive method, namely research conducted to examine an object, a condition or phenomenon, a group of people, with natural or real conditions. Trying to tell the current problem solving based on the data. The right data needs to be determined by informants who have competence and are in accordance with data needs (purposive). This study aims to describe in full and in detail the events or various phenomena studied regarding underage marriages. The results showed that the cause of the increase in underage marriages in the Religious Affairs Office of the Kebakkramat District was the concern of the parents because the child's relationship with the boyfriend was too close for fear that an act prohibited by the provisions of Islamic law would occur, namely adultery and other disgraceful acts. Another cause is because they are already pregnant, the parents marry off because their children are already working, they are considered ready to become husbands or heads of families or conversely ready to become wives or housewives. For couples who are not married, they should think more carefully about getting married, avoiding underage marriages. In order to realize the purpose of marriage, namely to form a happy and eternal family or household based on Belief in the One and Only God.